(untitled) (Lex Journal : Kajian Hukum dan Keadilan, 2025)
This research analyzes the challenges and harmonization between Islamic law and human rights. The research method used is the normative juridical method using statutory and conceptual approaches. The results showed that Islamic Law and Pancasila are two normative systems that have different characteristics. Still, both play an important role in shaping the framework of harmonization of human rights in Indonesia. Islamic law, as a manifestation of the religious values of Muslims, and Pancasila, as the philosophical basis of the state, have similar goals, namely to realize a just, peaceful, and harmonious society. The role of Islamic law in this context can be seen through efforts to protect individual rights, create social justice, and strengthen tolerance between religious communities. Harmonization between Islamic family law and human rights principles is a challenging but possible process with an inclusive and contextual approach. Differences in interpretation between traditional sharia law and modern human rights standards can be bridged through a dynamic understanding of maqāṣid al-sharī’ah, the involvement of women in policy-making, and human rights education in society. Case studies in Indonesia, Tunisia, Egypt, and Saudi Arabia show that successful harmonization depends on the socio-political context, religious legitimacy, and public participation. Through interdisciplinary dialogue and institutional strengthening, this harmonization can create a fair family law system that respects the human rights of every individual.